Pengaruh Perubahan Kadar Air pada Sifat-Sifat Tanah Organik yang distabilisasi dengan Limbah Karbit dan Abu Ampas Tebu - HATMOKO, John Tri; HANDOKO, Luky (Fakultas Teknik Universitas Katolik Santo Thomas, 2019)
Research on organic soil stabilization utilizing materials such as cement, lime, rice husk ash, fly ash, bagasse ash to change soil shear behavior has been widely carried out to this date. However, not many researchers have studied the changes in water content in organic soils that have been stabilized with such materials, especially on the changes in soil physical properties. This study aims to find out the effect of changes in water content in physical properties including: volume weight (Î³), specific gravity (G), water content (w), void ratio (e), degree of acidity (pH) and content organic (O). A series of tests was conducted, namely the chemical composition of: organic soil test (TO), carbide waste (CCR), and bagasse ash (AAT), and testing for the physical properties of organic soil. Further, additional material (60% CCR and 40% AAT) was added to the soil in proportions: 5, 10, 15, 20, 25 and 30% combined with different initial water contents (498, 548 and 598%) and curing time: 7, 14, 21 and 36 days. Then, we conducted test for physical properties of the soil that has been stabilized. The physical and chemical properties of the soil change subject to added material content and ripening time. At high water content, the change is more significant than at lower water content. The volume weight, specific gravity, and acidity of the soil increases while the void ratio and soil organic content decrease. The optimal content of added material is 20% with an optimal time of curing 21 days